An ocean of data The potential of data on vessel traffic - Pilgrim, Graham (OECD Statistics Working Papers, 2024)
Rising uncertainties and geo-political tensions, together with increasingly complex trade relations have increased the demand for monitoring global trade in a timely manner. Although it was primarily designed to ensure vessel safety, information from the Automatic Information System, which allows for the tracking of vessels across the globe, is particularly well suited for providing insights on port activity and maritime trade developments, which accounts for a large share of global trade. Data are available in quasi real time but need to be pre-processed and validated. This paper contributes to existing research in this field in two major ways. First, it proposes a new methodology to identify ports, at a higher level of granularity than in past research. Second, it builds indicators to monitor port congestion and trends in maritime trade flows and provides more granular information to better understand those flows. Those indicators will still need to be refined, by complementing the AIS database with additional data sources, but already provide a useful source of information to monitor trade, at the country and global levels